Neuroprotective Effects of Exercise Postconditioning After Stroke via SIRT1-Mediated Suppression of Endoplasmic Reticulum (ER) Stress - Li, Fengwu; Geng, Xiaokun; Lee, Hangil; Wills, Melissa; Ding, Yuchuan (Frontiers in Cellular Neuroscience, 2021)
While it is well-known that pre-stroke exercise conditioning reduces the incidence of stroke and the development of comorbidities, it is unclear whether post-stroke exercise conditioning is also neuroprotective. The present study investigated whether exercise postconditioning (PostE) induced neuroprotection and elucidated the involvement of SIRT1 regulation on the ROS/ER stress pathway. Adult rats were subjected to middle cerebral artery occlusion (MCAO) followed by either: (1) resting; (2) mild exercise postconditioning (MPostE); or (3) intense exercise postconditioning (IPostE). PostE was initiated 24 h after reperfusion and performed on a treadmill. At 1 and 3 days thereafter, we determined infarct volumes, neurological defects, brain edema, apoptotic cell death through measuring pro- (BAX and Caspase-3) and anti-apoptotic (Bcl-2) proteins, and ER stress through the measurement of glucose-regulated protein 78 (GRP78), inositol-requiring 1α (IRE1α), protein kinase RNA-like endoplasmic reticulum kinase (PERK), activating transcription factor 6 (ATF6), C/EBP homologous protein (CHOP), Caspase-12, and SIRT1. Proteins were measured by Western blot. ROS production was detected by flow cytometry.Compared to resting rats, both MPostE and IPostE significantly decreased brain infarct volumes and edema, neurological deficits, ROS production, and apoptotic cell death. MPostE further increased Bcl-2 expression and Bcl-2/BAX ratio as well as BAX and Caspase-3 expressions and ROS production (*p < 0.05). Both PostE groups saw decreases in ER stress proteins, while MPostE demonstrated a further reduction in GRP78 (***p < 0.001) and Caspase-12 (*p < 0.05) expressions at 1 day and IRE1α (**p < 0.01) and CHOP (*p < 0.05) expressions at 3 days. Additionally, both PostE groups saw significant increases in SIRT1 expression.In this study, both mild and intense PostE levels induced neuroprotection after stroke through SIRT1 and ROS/ER stress pathway. Additionally, the results may provide a base for our future study regarding the regulation of SIRT1 on the ROS/ER stress pathway in the biochemical processes underlying post-stroke neuroprotection. The results suggest that mild exercise postconditioning might play a similar neuroprotective role as intensive exercise and could be an effective exercise strategy as well.